2019
DOI: 10.1002/stc.2381
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based concrete crack assessment using mask and region‐based convolutional neural network

Abstract: Recently, many countries have investigated replacing conventional visual inspection with computer-vision-based inspection to enhance the efficiency, speed, and objectivity of inspection. This paper presents a novel crack assessment framework for concrete structures that detects cracks using mask and region-based convolutional neural network (Mask R-CNN) and quantifies cracks using a few morphological operations on the detected crack masks. In this study, a Mask R-CNN is trained for crack detection using 1,102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(116 citation statements)
references
References 48 publications
(61 reference statements)
0
109
0
Order By: Relevance
“…Unlike morphological signal processing, a one‐dimensional structural element is not frequently used for morphological image filtering, 33 so a rectangular structural element is introduced into the closing operator. The effect of the closing is to enlarge the boundaries of the foreground (bright) regions in an image and shrink the background colour holes in these regions 34 . Therefore, the bright details, which correspond to wheelset bearing fault features, are highlighted after morphological closing.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Unlike morphological signal processing, a one‐dimensional structural element is not frequently used for morphological image filtering, 33 so a rectangular structural element is introduced into the closing operator. The effect of the closing is to enlarge the boundaries of the foreground (bright) regions in an image and shrink the background colour holes in these regions 34 . Therefore, the bright details, which correspond to wheelset bearing fault features, are highlighted after morphological closing.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Among these aspects, the algorithm for crack detection has been most actively researched. According to the Korean government policy, the acceptable width of cracks in concrete structures is less than 0.3 mm [10]. Therefore, most of the existing studies were focused on detecting micro-cracks.…”
Section: B Related Research 1) Crack Detection Without Deep Learningmentioning
confidence: 99%
“…Recently, Xue and Li applied a region‐based CNN model to find cracks and leakage within tunnel lining and demonstrated that the accuracy of crack detection was about 86% with their proposed CNN model based on GoogLeNet . Kim and Cho introduced a mask‐ and region‐based CNN model with which they were able to detect cracks wider than 0.3 mm. During the feature map extraction process, an additional segmentation layer, where the pixels within a proposed bounding box are classified in detail, was activated to delineate the cracks within a box.…”
Section: Literature Reviewmentioning
confidence: 99%